A METHODOLOGICAL FRAMEWORK FOR THE DEVELOPMENT OF COMMUNICATIVE COMPETENCE IN DIGITAL LEARNING ENVIRONMENTS (KONFERENSIYA, 2025)
The rapid digitalization of education has significantly transformedforeign language teaching and learning practices. Within this context, thedevelopment of communicative competence remains a central objective of languageeducation, requiring reconsideration of traditional methodological approaches. Thisarticle proposes a methodological framework for developing communicativecompetence in digital learning environments. Drawing on communicative languageteaching, competence-based education, and digital pedagogy, the study analyzes thestructural components of communicative competence and identifies effectivemethodological tools for its development in online and blended learning contexts.The findings emphasize the role of interactivity, multimodality, learner autonomy,and formative assessment in enhancing communicative outcomes in digitalenvironments.